Administration of Parthenolide extract (ACT001) improved autophagy and attenuate inflammatory in Rats with ARDS - Qiang Fu; Xuan Liu; Na Shen; Yanbo Di; Hewei Zhang; Chao Du; Tao Fang; Jianshuang Guo (Elsevier, 2022)
Introduction: ACT001 is widely used for the treatment of glioblastomas, breast cancers, and leukemic and the mechanism underlying the effect is anti-inflammatory. However, whether ACT001 has any effects on acute respiratory distress syndrome (ARDS) is not clear. Objectives: To investigate whether ACT001 helps to reduce mortality and pneumonedema after ARDS, and explore whether the mechanism is related to balance autophagy and inflammatory response. Methods: In this study, a rat model based on CLP was used to explore the potency of ACT001 in ARDS. The expression of the autophagy-related protein, lung injuries, cytokines, and inflammatory-related protein was assessed. Results: Compared with CLP group, ACT001 improved the survival rate, and lung wet-to-dry weight ratio. ACT001 activates autophagy, which is involved in the pathophysiologic process of sepsis, balancing the cytokine excessive release and lung injury in ARDS. Conclusion: ACT001 reduces mortality through improved autophagy and attenuates inflammation after ARDS.